POFA: A Potential Partial Cement Replacement Material in Oil Palm Shell Lightweight Aggregate Concrete - Khairunisa, Muthusamy; Nur Azzimah, Zamri (Trans Tech Publications, Switzerland, 2014)
Today, the necessity of environmental awareness and enforcement is more demanding and crucial than ever before. Environmental protection encompasses not only pollution but also sustainable development and conservation of natural resources and the eco-system. As a conclusion, protection and preservation of environment is still a pressing issue. This issue on environmental preservations and sustainability all over the world has lead to innovations of new material using by-products generated from various sectors such as palm oil industry. One of the potential recycle materials from palm oil industry is palm oil fuel ash which contains siliceous compositions and reacted as pozzolans to produce a stronger and denser concrete. Palm oil fuel ash (POFA) is by-product obtained by burning of fibers, shells and empty fruit bunches as fuel in palm oil mill boilers. Apart from POFA, oil palm shell (OPS), which also from oil palm waste has been used as lightweight aggregates resulting from never ending research conducted. In this investigation, these two types of waste were collected from the same palm oil mills in Kuantan, Malaysia and were both utilized inside lightweight aggregate concrete. By incorporating POFA and OPS as partial cement and coarse aggregate replacement, lightweight aggregate concrete with 35 MPa can be produced and is also significantly higher than control OPS concrete.